CLINICAL FEATURES CYTOMEGALOVIRUS INFECTION IN PREGNANT HIV-INFECTED WOMEN - Y. G. Shakhverdyan (Кубанский научный медицинский вестник, 2016)
Conducted comprehensive monitoring of pregnancy in 254 HIV-infected women of Krasnodar region with an average age at the time of taking the registration of pregnancy - 26,9 ± 0,3 years and gestational age 19,2 ± 0,5 weeks. The control group consisted of 116 pregnant women without HIV infection, randomized with a core group for age and pregnancy. In 220 (90,5 %) HIV-infected pregnant women diagnosed with latent CMV infection, primary - in 5 (2,1 %) and reactivate - in 18 (7,4 %). Equally often been infected with cytomegalovirus pregnant HIV-infected pregnant women without HIV infection (95,7 % and 96,5 %, Q≤0,5). Reactivate forms of CMV infection was significantly less often observed in pregnant women with HIV infection (7,1 % vs 27,6 %, Q≥0,5). The frequency of clinical forms of CMV infection compared with the age of HIV-infected pregnant women, with the duration and stage of HIV infection rates of HIV viral load and levels of CD4, anti-retroviral therapy, with the term of pregnancy, obstetric history. It was found that the incidence of CMV infection in pregnant women with HIV infection in process of a growing of patients, increasing the duration of HIV infection and the stage of its flow, more frequent multiplicity of pregnancy, reduce CD4+ T-lymphocytes, increase in HIV RNA. Reactivated forms of CMV infection was significantly more common in pregnant women with HIV infection at the lowest rates of CD4+ T-lymphocytes, maximal HIV viremia, delay in onset of perinatal antiretroviral prophylaxis. The frequency and variety of clinical forms of CMV infection in pregnant women with HIV infection do not depend on the well-being of obstetric history, as well as the number of co-ToRCH-infections.